Conceptual study on Grid-to-Vehicle (G2V) wireless power transfer using single-phase matrix converter - Muhammad Qusyairi Iqbal Mohd Zamani; Rahimi Baharom; Dalina Johari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the conceptual study on grid-to-electric vehicle (G2V) wireless power transfer (WPT) using Single Phase Matrix Converter (SPMC). In this work, the SPMC is used as a direct AC to AC converter to convert the input supply voltage at 50 Hz frequency to the output of 20 kHz to meet the WPT switching frequency operation of the transmitter and receiver coils. The high frequency AC voltage of the receiver coil is then rectified to a DC form by using SPMC. Through the proposed system, the battery of an electric car can be charged wirelessly, thus removing the annoying wires of the conventional electric vehicle charging system. The reduction in size of the charging system, power losses and optimum efficiency are among the advantages of the proposed system. MATLAB/Simulink (MLS) has been used to simulate the proposed model. Selected simulation result are presented to verify the proposed work.